Respiratory mechanics in infants with severe bronchiolitis on controlled mechanical ventilation - Pablo Cruces; Sebastián González-Dambrauskas; Julio Quilodrán; Jorge Valenzuela; Javier Martínez; Natalia Rivero; Pablo Arias; Franco Díaz (BMC Pulmonary Medicine, 2017)
Abstract Background Analysis of respiratory mechanics during mechanical ventilation (MV) is able to estimate resistive, elastic and inertial components of the working pressure of the respiratory system. Our aim was to discriminate the components of the working pressure of the respiratory system in infants on MV with severe bronchiolitis admitted to two PICU’s. Methods Infants younger than 1 year old with acute respiratory failure caused by severe bronchiolitis underwent neuromuscular blockade, tracheal intubation and volume controlled MV. Shortly after intubation studies of pulmonary mechanics were performed using inspiratory and expiratory breath hold. The maximum inspiratory and expiratory flow (QI and QE) as well as peak inspiratory (PIP), plateau (PPL) and total expiratory pressures (tPEEP) were measured. Inspiratory and expiratory resistances (RawI and RawE) and Time Constants (KTI and KTE) were calculated. Results We included 16 patients, of median age 2.5 (1–5.8) months. Bronchiolitis due to respiratory syncytial virus was the main etiology (93.8%) and 31.3% had comorbidities. Measured respiratory pressures were PIP 29 (26–31), PPL 24 (20–26), tPEEP 9 [8–11] cmH2O. Elastic component of the working pressure was significantly higher than resistive and both higher than threshold (tPEEP – PEEP) (P < 0.01). QI was significantly lower than QE [5 (4.27–6.75) v/s 16.5 (12–23.8) L/min. RawI and RawE were 38.8 (32–53) and 40.5 (22–55) cmH2O/L/s; KTI and KTE [0.18 (0.12–0.30) v/s 0.18 (0.13–0.22) s], and KTI:KTE ratio was 1:1.04 (1:0.59–1.42). Conclusions Analysis of respiratory mechanics of infants with severe bronchiolitis receiving MV shows that the elastic component of the working pressure of the respiratory system is the most important. The elastic and resistive components in conjunction with flow profile are characteristic of restrictive diseases. A better understanding of lung mechanics in this group of patients may lead to change the traditional ventilatory approach to severe bronchiolitis.